Splintered body image (2006)
Body image presentation, which made painting morevisual in the 20th century, offers visions of splinteredbodies in different versions of its extention in space andin its proyection in time. This splintered vision in visualpainting was structured by diverse factors, such as theearlier development of photography, and later by audiovisual,videography and rising virtual media. Painting´sclose-up shots on corporal action in the middle of the20th century, allowed us to question new paradigms ofcontemporary corporal experience, not only from theart field itself, but also, from the social and personalperceptual body experience.